Yttria-stabilized barium zirconate surface reactivity at elevated temperatures. (September 2020) - Welander, Märtha M.; Goettlich, Daniel J.; Henning, Tanner J.; Walker, Robert A.
Abstract : Abstract: Material changes in yttrium-doped barium zirconate, BaZr0.8 Y0.2 O3– x, were studied using in situ Raman spectroscopy and ex situ x-ray photoelectron spectroscopy analysis. During in situ Raman analysis, samples were heated to temperatures of 300–600 °C and exposed to both dry and humidified H2 atmospheres. At the lower temperatures (300–450 °C), a new vibrational peak appears in the Raman spectra during exposure to humidified H2 . The appearance of this feature is reversible, dependent on previous sample history, and possibly results from new, secondary phase formation or lattice distortion.